Whose rationality? : A response to Fekri Hassan - Hodder, Ian
In December 1997 we published Fekri Hassan's comments on Ian Hodder's 'Reflexive excavation methods' (ANTIQUITY 71: 1020Ð25). Ian Hodder responds here to the criticisms and defends his position.